Modeling and Measurement of Reflected Signals with u-Doppler Effect from Various Targets using a Pulse Radar - Jordán, Josef (IEEE (Institute of Electrical and Electronics Engineers), 2023)
The aim of this research is to develop a mathematical model that accurately describes the magnitude and phase of the reflected signal and the Doppler shifts caused by rotating parts of various radar targets. To ensure the validity of the model, a comparison with real-world measurements is performed. The primary focus of the publication is to compare simulated and measured Doppler signatures, known as u-Doppler signatures, to assess the accuracy and reliability of the proposed model. The research aims to provide a better understanding of the dynamics of radar signals reflected by rotating objects. This can have an importance in fields such as surveillance, navigation, and defense.
Modelování a měření odražených signálů s u-Dopplerovým efektem od různých cílů pomocí pulzního radaru
Keywords: radar; doppler; u-doppler; drone; spectrogram; fan; propagation model; measurements; radar; doppler; u-doppler; dron; spektrogram; ventilátor; model šíření; měření